2002
DOI: 10.1016/s0006-3495(02)75585-9
|View full text |Cite
|
Sign up to set email alerts
|

Preformed Oligomeric Epidermal Growth Factor Receptors Undergo an Ectodomain Structure Change during Signaling

Abstract: Fluorescence resonance energy transfer (FRET) was used to reveal aspects of the mechanism of signal transduction by epidermal growth factor receptors (EGFR). The superpositions of epidermal growth factor (EGF), transforming growth factor-alpha (TGFalpha) and an antibody fragment (29.1) to the carbohydrate extremity of the receptor's ectodomain as measured by FRET, show that 14% of EGFRs in A431 cells are oligomerized before growth factor binding. After binding growth factor and signaling, these oligomers disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 60 publications
(113 reference statements)
8
86
1
Order By: Relevance
“…promote lateral signal propagation (Martin-Fernandez et al, 2002;Yu et al, 2002;Bader et al, 2009). Our observation that only a subset of BRI1-SERK3 heterooligomers is present after ligand depletion is comparable to findings for EGFR in mammalian cells, as demonstrated by Bader et al (2009).…”
Section: Discussionsupporting
confidence: 79%
“…promote lateral signal propagation (Martin-Fernandez et al, 2002;Yu et al, 2002;Bader et al, 2009). Our observation that only a subset of BRI1-SERK3 heterooligomers is present after ligand depletion is comparable to findings for EGFR in mammalian cells, as demonstrated by Bader et al (2009).…”
Section: Discussionsupporting
confidence: 79%
“…Although several lines of evidence (3,4), support this view, both recent and earlier evidence (16)(17)(18)(20)(21)(22) have suggested that two aspects of the classical model need to be reconsidered: (i) inactive receptors are not necessarily monomeric, such that (ii) higher-order clusters of inactive and/or activated receptors may exist. We chose the novel technique of N&B analysis (23) to investigate these issues.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest the existence of preformed (i.e., ligand-independent, ErbB1 receptor dimers) (16,17) or larger aggregates (18) in addition to the classical dimers formed upon ligand-induced activation of receptor monomers. However, the different techniques, cell types, and conditions of the experiments have resulted in conflicting and contradictory results.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…This model has been supported by crystal structures of the extracellular domain of EGFR (7,8) as well as by reports of EGFR dimerization after stimulation with EGF. However, numerous studies have also reported the presence of EGFR dimers or even larger oligomers in the membranes of resting cells (9)(10)(11)(12)(13). The presence of preformed EGFR dimers and oligomers indicates that regulation of EGFR signaling is more complex than implied by the model outlined above (Fig.…”
Section: Introductionmentioning
confidence: 93%